Design of ALU System Using Novel PMOS and NMOS for Low Power and High Speed Applications - Babu CH, Ashok; V.R. Ravindra, J; Lalkishore, K (International Journal of Engineering and Technology, 2018)
This paper tailors 8 bit ALU for high speed and low power applications. In this design a novel PMOS and NMOS are used in place of conventional PMOS and NMOS. The main disadvantage of conventional PMOS and NMOS is low speed. With the technique of forward body biasing a novel PMOS and NMOS are derived and speed is improved. For each sub module of ALU power delay product percentage is calculated. Percentage improvement in power delay product of Novel ALU is shown in table 27.Â Â